ĐẶC ĐIỂM THÀNH PHẦN LOÀI THỰC VẬT ĐẶC TRƯNG VÀ PHÂN BỐ TRÊN CÁC ĐẢO THUỘC QUẦN ĐẢO TRƯỜNG SA, VIỆT NAM - Trần, Thị Thanh Hương; Lê, Xuân Đắc; Nguyễn, Đăng Hội; Đặng, Ngọc Huyền; Bùi, Văn Thanh; Nguyễn, Vũ Anh; Phạm, Mai Phương; Vũ, Đình Duy; Đỗ, Văn Hải (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
CHARACTERISTICS OF TYPICAL TERRESTRIAL PLANT SPECIES COMPOSITION AND DISTRIBUTION IN TRUONG SA ISLANDS, VIETNAM The study was conducted to determine the species composition and distribution characteristics of typical terrestrial plant species for the Truong Sa (Spratly) Islands. By research methods of field investigation reference to documents and expert opinions according to three groups: Typical natural species; Naturalized species and Common natural species has identified 75 species of typical terrestrial plants for the flora of the Truong Sa (Spratly) Islands, 58 genera, 29 families belonging to the Angiospermae, focusing on the Poaceae, Cyperaceae, Malvaceae, Fabaceae, Asteraceae, etc. There’re 7 life forms and 6 habitats were recorded with typical terrestrial plant species distribution. In which, the most concentrated in herbaceous life forms with 49 species (65.3%) and open place land in and around the island habitat with 38 species (50.7%). There are 6 groups of use values identified from typical terrestrial plant species, such as protection, ornamental, medicinal herbs, food, etc. of which the value of protection accounts for 56.0%, with 42/75 species.